Analisis Model Kepemimpinan Teory Path Goal Pada Lembaga Pendidikan Islam - Alkafi, Kurnia; Heriansyah, M Arie Firdaus; Syarifudin, Encep; Lughowi, Rifyah Ahmad; Asyibli, Basri (Jurnal Kependidikan, 2025)
This study aims to analyze the role of leadership in increasing the effectiveness of educational organizations through the application of Path-Goal Theory. The method used is a literature study, by collecting and analyzing information from various relevant written sources. The results show that effective leadership, which includes a directive, supportive, participatory, and achievement-oriented style, can improve the motivation and performance of organizational members. Leaders who are able to adapt their leadership style to the characteristics of subordinates and environmental situations will be more successful in achieving organizational goals. The implications of this study emphasize the importance of a deep understanding of subordinates' strengths and weaknesses, as well as the need to create a conducive work environment. Thus, the application of this theory can assist leaders in formulating more effective strategies to motivate and empower team members, thereby increasing the productivity and success of educational organizations in the future. This research is expected to be a reference for leaders in developing leadership styles that are in accordance with the context and needs of the organization.